A SOCIOLINGUISTIC ANALYSIS OF TABOO WORD CHARACTER IN MILKMAN NOVEL: Sociolinguistics, Taboo, Milkman Novel - Muhammad Ainul Yaqin (Fakultas Sastra Universitas Gresik, 2021)
Sociology is the objective and scientific study of humans in society, and of the social institutions and processes that exist in society. Linguistics is a field of science that studies language, or a field of science that takes language as its object of study. In sociolinguistics, taboo words are part of sociolinguistics related to language and society. The word taboo is a word that is not considered good by the public or is better avoided, because they mention facts that are considered rude and disrespectful, in this study using a literature study taken from the milkman novel using reading techniques and marking parts of the word taboo in novel and the results obtained are obsenity 4 taboo sentences, profanity 2 taboo sentences, vulgarity 3 taboo sentences, epithet 1 taboo sentence, and taboo sentences in milkman novels are sentences that are usually spoken to insult or give nicknames to others.